Consumer Psychological Factors and Impulse Buying: The Moderating Role of Mindfulness among Generation Z QRIS Users - Indah Riyani; Wenny Pebrianti; Nurul Komari; Bintoro Bagus Purmono; Harry Setiawan (Al-Qalam Institue, 2026)
The rapid adoption of QRIS-based digital payment systems has transformed Generation Z’s consumption patterns, particularly by increasing their tendency toward impulse buying. This study aims to examine the effects of spendception, cashless effect, and hedonic motivation on impulse buying, as well as the moderating role of mindfulness. This quantitative study involved 250 Generation Z respondents in Indonesia who had engaged in impulse buying using QRIS within the past six months. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results indicate that spendception, cashless effect, and hedonic motivation have positive and significant effects on impulse buying. Mindfulness weakens the influence of the cashless effect arising from transaction convenience and hedonic motivation driven by emotional pleasure. Conversely, mindfulness strengthens the effect of spendception on impulse buying, as a reduced perception of monetary loss makes transactional awareness insufficient to restrain purchasing impulses. These findings suggest that psychological processes in digital transactions are heterogeneous, depending on consumers’ cognitive and affective dynamics, and offer practical implications for consumers in managing impulsive purchasing tendencies in the era of digital payments.